A review of methods for determining structural fire severity—Part I: A historical perspective - MacIntyre, Jonathon D.; Abu, Anthony K.; Moss, Peter J.; Nilsson, Daniel; Wade, Colleen A. (Fire and materials, 2022)
Summary There is a risk of a building suffering unsustainable structural damage in the event of a large fire. Therefore, it is necessary to design buildings to withstand expected fires. A widely used simplified calculation method is the so‐called ‘time‐equivalence’ method. There are significant concerns about the suitability of this method. This paper is Part I of a twofold study examining the state of the art of time‐equivalence methods. The purpose of this paper is to provide a detailed background of the development of time‐equivalence methods since its first introduction in 1928 and to provide an initial high‐level assessment of the accuracy of these methods. A simple scoring system is used to assess the methods based on the accuracy of the analysis techniques used in their derivation. The study revealed that most methods do not account well for structural system response to fire exposure. While some time‐equivalence methods do yield accurate results, further analysis is required to fully assess their suitability.